Measurements of Volatile Organic Compounds During the COVID‐19 Lockdown in Changzhou, China - Andrew Jensen; Zhiqiang Liu; Wen Tan; Barbara Dix; Tianshu Chen; Abigail Koss; Liang Zhu; Li Li; Joost deGouw (Geophysical Research Letters)
Abstract The COVID‐19 outbreak in 2020 prompted strict lockdowns, reduced human activity, and reduced emissions of air pollutants. We measured volatile organic compounds (VOCs) using a proton‐transfer‐reaction mass spectrometry instrument in Changzhou, China from 8 January through 27 March, including periods of pre‐lockdown, strict measures (level 1), and more relaxed measures (level 2). We analyze the data using positive matrix factorization and resolve four factors: textile industrial emissions (62 ± 10% average reduction during level 1 relative to pre‐lockdown), pharmaceutical industrial emissions (40 ± 20%), traffic emissions (71 ± 10%), and secondary chemistry (20 ± 20%). The two industrial sources showed different responses to the lockdown, so emissions from the industrial sector should not be scaled uniformly. The quantified changes in VOCs due to the lockdowns constrain emission inventories and inform chemistry‐transport models, particularly for sectors where activity data are sparse, as the effects of lockdowns on air quality are explored.